Efficacy and Safety of Pegylated Interferon-α2A in Patients with Lamivudine-Resistant Hbeag-Positive Chronic Hepatitis B. Issue 6 (August 2013) - Suh, Dong Jin; Lee, Han Chu; Byun, Kwan Soo; Cho, Mong; Kweon, Young Oh; Tak, Won Young; Chon, Chae Yoon; Koh, Kwang Cheol; Lee, Young Sok
Background: Lamivudine resistance develops in up to 80% of patients with chronic hepatitis B (CHB) after 5 years of treatment. Cross-resistance between nucleoside/nucleotide analogues limits management options in these patients. To investigate the role of pegylated interferon-α2a as rescue therapy in these patients, the efficacy and safety of pegylated interferon-α2a between treatment-naive patients and lamivudine-resistant patients with hepatitis B e antigen (HBeAg)-positive CHB were compared. Methods: A total of 150 HBeAg-positive CHB patients were stratified according to prior treatment. Lamivudine-resistant patients ( n =64) and treatment-naive patients ( n =86) received pegylated interferon-α2a once-weekly for 48 weeks and were followed-up for an additional 24 weeks. Primary end points were HBeAg loss and HBV DNA <100, 000 copies/ml at end of follow-up. Results: A total of 65 (76%) treatment-naive patients and 49 (77%) lamivudine-resistant patients completed treatment and 24 weeks of follow-up. Rates of HBeAg loss were comparable at end of follow-up between treatment-naive patients and lamivudine-resistant patients (20.9% and 23.4%, respectively; P =0.8423). Similarly, rates of HBV DNA<100, 000 copies/ml were comparable at end of follow-up between treatment-naive patients and lamivudine-resistant patients (20.9% and 21.9%, respectively; P =1.000). There was no statistically significant difference in alanine aminotransferase normalization rates between treatment-naive patients and lamivudine-resistant patients (36.0% and 29.7%, respectively; P =0.4848). A total of one patient in each group achieved hepatitis B surface antigen (HBsAg) loss and seroconversion. The most common adverse events were those known to occur with pegylated interferon-α2a therapy, and safety profiles were similar between both patient populations. Conclusions: Pegylated interferon-α2a may be effective as a rescue therapy in patients with lamivudine-resistant HBeAg-positive CHB.